Pengaruh Segmenting, Targeting dan Positioning terhadap Keputusan Pembelian Produk Teh Organik Brew Me - NADIARINI, MADE RIZKI SRI; ANTARA, MADE; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
The Influence of Segmenting, Targeting and Positioning Strategies on Purchase Decisions for Brew Me Organic Tea Products Segmenting, Targeting and Positioning are elements of a marketing strategy that are used to help plan the right product marketing for a product. This is what Brew Me has done in formulating its marketing strategy in dealing with the problems it has, namely the decline in sales of Brew Me products in the Horeca segment due to the COVID-19 pandemic. This study then aims to analyze the effect of segmenting, targeting, and positioning on purchasing decisions using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach. The sample in this study was 200 respondents who were consumers of Brew Me. The results showed that the segmenting, targeting, and positioning variables had a significant influence on consumer decisions as evidenced by the p-values ??of each variable having a value of 0.000; 0.007; 0.000 with a standard error of 5%. This result means that if the implementation of indicators in the segmenting, targeting, and positioning variables is getting better, it will be able to improve the purchasing decisions of Brew Me consumers as well. The advice that can be given is to maintain the strategy that has been made by Brew Me, then Brew Me also needs to pay attention to the latest trends that are tailored to the product so that Brew Me products are more easily recognized by consumers in the retail, online and e-commerce markets.